Guidelines for the prediction and control of methane emissions on longwalls - Schatzel, Steven J.; National Institute for Occupational Safety and Health; Pittsburgh Research Laboratory (National Institute for Occupational Safety and Health) (Pittsburgh, PA : Department of Health and Human Services, Centers for Disease Control and Prevention, National Institute for Occupational Safety and Health, Pittsburgh Research Laboratory, 2008)
"Although longwall mining productivity can far exceed that of room-and-pillar mining, the total methane emissions per extracted volume associated with longwall sections are generally higher than those for continuous miner or pillar removal sections. Increased face advance rates, increased productivities, increased panel sizes, and more extensive gate road developments have challenged existing designs for controlling methane on longwalls. Methane control research by the National Institute for Occupational Safety and Health (NIOSH) recently examined a number of practices designed to maintain concentrations in mine air within statutory limits and consistently below the lower explosive limit. In this report, several practical guidelines are recommended for controlling longwall coalbed methane. All predictions are based on determinations made for the Pittsburgh Coalbed in southwestern Pennsylvania."
1. Reservoir modeling for predicting methane emissions in development headings (entries) -- 2. Controlling longwall face methane and development mining emissions: predicted improvements using in-seam boreholes -- 3. Characterizing and forecasting longwall face methane emission rates for longer longwall faces -- 4. Predicting methane emissions from longer longwall faces by analysis of emission -- contributors -- 5. Development of numerical models to investigate permeability changes, distributions, and gas emissions around a longwall panel -- 6. Methane emission control during mining of longwall panels using gob gas ventholes -- 7. The application of gob gas ventholes to control methane in wider longwall panels and gobs -- 8. Induced fracturing and coalbed gas migration in longwall panel overburden: the NIOSH borehole monitoring experiment6 -- Practical guidelines for controlling longwall coalbed methane.
Title from title screen (viewed June 27, 2008).
Includes bibliographical references (pages 80-83).
Keywords: Coalbed methane; Longwall mining -- Safety measures; Methane; Mine gases